2011
DOI: 10.1111/j.1468-3083.2011.04154.x
|View full text |Cite
|
Sign up to set email alerts
|

Sun behaviour patterns and perception of illness among melanoma patients

Abstract: Participants in control group perceive melanoma as a more serious illness than patients who think that melanoma has mild symptoms, is easy to cure and control, has moderate consequences and lasts relatively long. Both melanoma patients and participants in the control group show relatively good sun behaviour patterns and slightly negative attitudes towards sun protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Few studies have included a control group[23, 24, 26, 35]; the largest to date compared 156 melanoma survivors to 11408 respondents without cancer who participated in 2005 and 2007 National Cancer Institute Health Information National Trends Surveys (HINTS). [26] Notably, the results were similar to our study, though HINTS respondents reported slightly lower frequencies of sunscreen use.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have included a control group[23, 24, 26, 35]; the largest to date compared 156 melanoma survivors to 11408 respondents without cancer who participated in 2005 and 2007 National Cancer Institute Health Information National Trends Surveys (HINTS). [26] Notably, the results were similar to our study, though HINTS respondents reported slightly lower frequencies of sunscreen use.…”
Section: Discussionmentioning
confidence: 99%
“…This study was designed to provide a basis for strategies to increase sun‐protective behaviours in patients who might not otherwise practise them. Because patients with a personal history of skin cancer are at particularly high risk for subsequent NMSC, and are also known to practise increased sun‐protective behaviours, 19 496 participants who reported a history of skin cancer, including Bowen disease, were excluded. Thus, the final study sample consisted of 198 patients with no personal history of skin cancer, in order to best approximate the first dermatology appointment after transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…However, few studies have applied the BIPQ to cancer patients, and no studies have yet applied it to HSCT recipients. Evidence suggests that patients' positive perceptions of their disease and side effects accompany a clearer understanding of their illness and enhanced self-management (Zivkovic et al, 2012). This sub-study of the PROVIVO study was the first to administer the German version of the BIPQ in long-term survivors (Kirsch et al, 2015).…”
Section: Introductionmentioning
confidence: 96%